STRATEGI PENGEMBANGAN USAHA COKELAT PASTA PADA INDUSTRI RUMAH COKELAT DI KOTA PALU - Risdayani,, Risdayani, (AGROTEKBIS, 2016)
The purpose of the research is to find out the strategy of Homes industry development of Chocolate in Palu located on Setia Budi street Eastern Palu Central Sulawesi. This research was carried out in April 2016. The respondents in this study were as much as 4 people consisting of 1 person of leadership, 1 employee and 2 consumers. Analysis tool used is the SWOT analysis. The results showed that, 1) Business Development Strategy of Brown paste can be applied to the Brown home industry by utilizing the entire force to seize and exploit the opportunities (S-O strategies). 2) Position quadrants are on one or on the position of the power strategy consists of three strategies, namely utilizing the original flavour of the cocoa beans in order to capture opportunities no similar products, utilizing fat as raw cocoa chocolate making in order to capture the opportunities of the opening of the market, continue to maintain and improve the quality of products and an experienced workforce in order to capture the presence of government programs.